2017
DOI: 10.18295/squmj.2017.17.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Educational Activities in Reducing Pre-Analytical Laboratory Errors: A quality initiative

Abstract: Objectives: Pre-analytic errors during diagnostic laboratory investigations can lead to increased patient morbidity and mortality. This study aimed to ascertain the effect of educational nursing activities on the incidence of pre-analytical errors resulting in non-conforming blood samples. Methods: This study was conducted between January 2008 and December 2015. All specimens received at the Haematology Laboratory of the Sultan Qaboos University Hospital, Muscat, Oman, during this period were prospectively col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…A study investigating the impact of educational training among nurses in a hospital in Oman in 2017 showed about 75.9% improvement in sample quality after re-training. 30 The availability of specially trained phlebotomy personnel within a facility is important not just for proper blood sample collection, but also to ease the workload on the already overworked nurses and doctors, who may tend to rush sample collection due to the increased workload. 30 Haemolysed samples certainly pose a serious challenge for clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study investigating the impact of educational training among nurses in a hospital in Oman in 2017 showed about 75.9% improvement in sample quality after re-training. 30 The availability of specially trained phlebotomy personnel within a facility is important not just for proper blood sample collection, but also to ease the workload on the already overworked nurses and doctors, who may tend to rush sample collection due to the increased workload. 30 Haemolysed samples certainly pose a serious challenge for clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…30 The availability of specially trained phlebotomy personnel within a facility is important not just for proper blood sample collection, but also to ease the workload on the already overworked nurses and doctors, who may tend to rush sample collection due to the increased workload. 30 Haemolysed samples certainly pose a serious challenge for clinical laboratories. 7 Contamination by EDTA-K anticoagulant as a cause of pseudohyperkalaemia accounted for 6.3% of the potassium rejections in this study and is common in clinical chemistry laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned methods generally exert good accuracy and reliability. On the other hand, common laboratory assays require reliable and expensive equipment and infrastructure, systematic quality control, instrument services and experienced and educated personnel to be performed [ 43 , 44 , 45 , 46 , 47 ]. During the COVID-19 pandemic, simple means of diagnosing the disease or detecting the presence of covid antigens or other markers were highly desired and were helpful when available in sufficient numbers and at a low price at the same time.…”
Section: Current Point-of-care Tests For Covid-19mentioning
confidence: 99%
“…It was also reported that an error in sample identification reduced by 0.056% and led to 96.55% improvement. A positive impact of this intervention was a 127.84% increase in the total 21 number of specimens received.…”
mentioning
confidence: 99%